Opinions of Polish occupational medicine physicians on workplace health promotion - Puchalski, Krzysztof; Korzeniowska, Elżbieta; Pyżalski, Jacek; Wojtaszczyk, Patrycja (Nofer Institute of Occupational Medicine, 2005)
Objectives: According to the current Polish legislation on occupational health services, occupational medicine physicians should perform workplace health promotion (WHP) activities as a part of their professional work. The concept of workplace health promotion or health promotion programs, however, has not been deﬁned in this legislation in any way. Therefore, two essential questions arise. First, what is the physicians’ attitude towards workplace health issues and second, what is actually carried out under the label of health promotion? The main objective of the research described in this paper was to answer these questions. Materials and Methods: The survey was carried out by the National Center for Workplace Health Promotion in 2002. A questionnaire prepared by the Center for the purpose of this survey was sent to a random sample of occupational medicine physicians. Results: The results of the survey showed that 53% of occupational medicine physicians consider WHP just as a new name for prophylactics. On the other hand almost all of the respondents (94%) agree that occupational medicine physicians should perform WHP activities and ﬁnd them useful in improving patients’ health (78%). The main obstacle for the development of this activity in the perception of physicians is the lack of interest in workplace health promotion among employers (86%). Conclusions: In the modern understanding of workplace health promotion concept this type of intervention includes not only safety measures and health education, but also a profound organizational change that allows employers, employees and social partners to improve wellbeing of people at work. Each of such projects should facilitate changes necessary to create a health promoting workplace. It also needs a skilled leader – well trained and aware of a multidisciplinary dimension of WHP interventions. Occupational medicine specialists should become natural partners of employers and employees. The majority of the occupational medicine physicians, however, are not sufﬁciently prepared to carry out workplace health promotion programs
Keywords: promocja zdrowia; health promotion; promocja zdrowia w miejscu pracy; workplace health promotion; zdrowie zawodowe; occupational health; lekarz medycyny pracy; occupational health physician